Injuries associated with electronic nicotine delivery systems: A systematic review. Issue 4 (October 2020) - Vyncke, Tom; De Wolf, Edward; Hoeksema, Henk; Verbelen, Jozef; De Coninck, Petra; Buncamper, Marlon; Monstrey, Stan; Claes, Karel E.Y.
Abstract : BACKGROUND: Since its introduction on the market in 2007, the number of reports on injuries caused by the overheating, ignition, or explosion of electronic nicotine delivery systems (ENDSs) has increased significantly. These injuries appear to have different causes, the most important one being lithium-ion battery overheating to the point of ignition or explosion. METHODS: A literature search for all relevant studies concerning ENDS-related traumatic injuries of all kinds was conducted, according to the Preferred Reporting Items for Systematic Reviews and Meta-analyses protocol. The search started with the first introduction of ENDSs in 2007 and ended February 2020. Articles included were reports on patients who sustained flame, chemical, or traumatic injuries of the skin, soft tissue, and/or bone, related to the use of ENDSs. RESULTS: This systematic review includes 180 patients from 41 case series and reports, published between 2016 and 2020. The mean age was 30.8 years (range, 17–59 years) with an overall male predominance (168 of 180 patients, 93%). In most injuries, multiple anatomical sites were affected, with the thigh/lower limb being the most commonly injured area (77%) followed by the upper limb/hand (43%). Eighty-two patients (51%) required a surgical treatment, 70 patients (43%) were managed conservatively with dressings or ointments, and 9 patients (6%) underwent enzymatic debridement. Thirty-five percent of all patients underwent skin grafting. CONCLUSION: Injuries from overheating, ignition, or explosion of ENDSs are an emerging, underreported, and underresearched issue. There is a need for increased regulation of ENDSs and improved surveillance of related injuries. Both health care providers and consumers should be made aware of the risks and be advised about how to safely handle these devices. In contrast to other articles, this systematic review includes all types of injuries related to ENDS overheating, ignition, and explosion. To our knowledge, this is the most extensive systematic review performed to date. LEVEL OF EVIDENCE: Review article, level III.